2017
DOI: 10.1002/imhj.21677
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on Fathers’ Play: Measurement, Conceptualization, Culture, and Connections With Child Development

Abstract: The diverse set of studies in this special issue on fathers' play includes empirical research from several countries, observational measures of play, and multiple children's outcomes, including language, negativity, social competence, aggression and internalizing problems. The chief conclusion across studies is that the role of paternal play is important in various domains of child development. This is encouraging, yet also disturbing given the results of the State of the World's Fathers: Time for Action repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…Na međuodnos roditelja, kao i njihov odnos prema djetetu, utječu različiti biološki i kulturološki čimbenici poput hormonalnih promjena (Guder i Ata, 2018), zdravstvenog stanja (Palkowitz, 2002), životne dobi (Parke, 2004), nasljeđa (Stephens, 2009;Seligman i Darling, 1997) i sustava vrijednosti (Goldscheider, Olah i Puur, 2010). Pokazalo se kako na aktivnu uključenost oca u odgoj utječu i neki drugi čimbenici, poput odnosa s partnericom (Majdandžić, 2017) (Gaunt, 2006).…”
Section: Roditeljsko Ponašanje Prema Djetetu S Poremećajem Iz Spektra...unclassified
“…Na međuodnos roditelja, kao i njihov odnos prema djetetu, utječu različiti biološki i kulturološki čimbenici poput hormonalnih promjena (Guder i Ata, 2018), zdravstvenog stanja (Palkowitz, 2002), životne dobi (Parke, 2004), nasljeđa (Stephens, 2009;Seligman i Darling, 1997) i sustava vrijednosti (Goldscheider, Olah i Puur, 2010). Pokazalo se kako na aktivnu uključenost oca u odgoj utječu i neki drugi čimbenici, poput odnosa s partnericom (Majdandžić, 2017) (Gaunt, 2006).…”
Section: Roditeljsko Ponašanje Prema Djetetu S Poremećajem Iz Spektra...unclassified
“…Na međuodnos roditelja, kao i njihov odnos prema djetetu, utječu različiti biološki i kulturološki čimbenici poput hormonalnih promjena (Guder i Ata, 2018), zdravstvenog stanja (Palkowitz, 2002), životne dobi (Parke, 2004), nasljeđa (Stephens, 2009;Seligman i Darling, 1997) i sustava vrijednosti (Goldscheider, Olah i Puur, 2010). Pokazalo se kako na aktivnu uključenost oca u odgoj utječu i neki drugi čimbenici, poput odnosa s partnericom (Majdandžić, 2017) (Gaunt, 2006).…”
Section: Roditeljsko Ponašanje Prema Djetetu S Poremećajem Iz Spektra...unclassified
“…It has been suggested that fathers spend a greater portion of their time playing with their children than doing any other activity [ 5 ]. While both mothers and fathers engage in play with their children [ 6 , 7 ], past research has primarily focussed on maternal influences on child development [ 8 ], with only one-third of parent–child play interaction research being conducted with fathers [ 4 ]. However, in recent decades, the social movement of involved fatherhood has stimulated a research focus on fathers [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%